Piezoceramic Sensors - Sharapov, Valeriy; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book presents the latest and complete information about various types of piezosensors. A sensor is a converter of the measured physical size to an electric signal. Piezoelectric transducers and sensors are based on piezoelectric effects. They have proven to be versatile tools for the measurement of various processes. They are used for quality assurance, process control and for research and development in many different industries. In each area of application specific requirements to the parameters of transducers and sensors are developed. The book presents the fundamentals, technical design and details and practical applications. Methods to design piezosensors are described, allowing to create sensors with unique properties. New methods to measure physical sizes and new constructions of sensors including large area of piezosensors are described in this book. This book is written for specialists in transforming hydroacoustics, non-destructive control, measuring technique, sensors development for automatic control and also for graduate students.
Preface -- General information about piezoelectric sensors -- Monomorph piezoceramic elements -- Spatial energy force structure of piezoceramic transducers -- Measuring chains of piezoelectric sensors -- Feedback in the piezoceramic sensors -- Bimorph and threemorph piezoelements -- Devices by control and diagnostics of bimorph piezoelements -- Piezomagnetic sensors -- Hydroacoustic transducers -- Transducers for non-destructive control -- Sensors of tones of Korotkov -- Electroacoustic transducers -- Piezoceramic accelerometers -- Resonant piezoceramic sensors -- Sensors with piezoelements in electric filters -- Piezoceramic scanners for probe nanomicroscopes.
Keywords: Chemistry; Microreactors; Engineering; Chemistry; Microengineering; Nanotechnology and Microengineering; Ceramics, Glass, Composites, Natural Methods; Signal, Image and Speech Processing; Applied and Technical Physics